Three Case Reports of Sudden Death as a Result of Hemorrhage Related to Vascular Malformation of Brain - Pakiş, Işıl; Turan, Arzu Akçay; Karayel, Ferah; Sav, Aydın; Çetin, Gürsel (The Bulletin of Legal Medicine, 2003)
Vessel abnormalities seen in the central nervous system are the result of vascular malformations in brain and can be observed in various forms like little lesions determined at the autopsy to lesions leading to fatal intracranial haemorrhages. Our study includes three sudden death cases which were autopsied between 1998-2003 at the Morgue Specialization Department of the Council of Forensic Medicine. Cause of death was subarachnoidal and intracerebral haemorrhage due to vascular malformation in brain for all three cases. Age of our cases were between 16 to 29, two of them were male, and one was female. Macroscopic examination revealed softening of brain and cerebellum consistency, and inner parenchymal, intraventricular and subarachnoid hemorrhage areas with localisation on right parietal lobe in one case, and with localisation on cerebellum and brain stem in two cases. Microscopic examination showed folded vessel structures, connected and back to back with each other in brain parenchyma. Some of the vessels were thin walled and venous, but most of them were composed of ambigious vessel structures. Neural tissue could be differentiated between vessels. According to macroscopic and microscopic findings, the cases were considered as arteriovenous malformation, and related were subarachnoid and intracerebral hemorrhage. Death occured as pathological cerebral hemorrhage related with vascular malformation. These cases with various clinical progress, and occasionally clinically asyptomatic, can be seen as a cause of sudden death in our forensic medical practice. The aim of this case report is to emphasize the medical and legal importance of autopsy in uncertainty of death cause. Key words: Arteriovenous malformation, sudden death, autopsy